2021
DOI: 10.1371/journal.pone.0253634
|View full text |Cite
|
Sign up to set email alerts
|

State-trait interactions in regulatory focus determine impulse buying behavior

Abstract: Little research has focused on motivational state-trait interactions to explain impulse buying. Although the trait chronic regulatory focus has been linked to impulse buying, no evidence yet exists for an effect of situational regulatory focus and no research has examined whether the fit of chronic and situational regulatory focus can influence impulse buying with actual consumptive consequences rather than purchase intentions. Two laboratory experiments (total N = 250) manipulated situational regulatory focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Consumer resources are significant predictors of impulse buying (Atulkar & Kesari, 2018; Krishna et al, 2021). A shopping trip budget determines a consumer's buying power, and a larger budget can trigger positive emotions resulting in impulse buying (Badgaiyan & Verma, 2015; Chang et al, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer resources are significant predictors of impulse buying (Atulkar & Kesari, 2018; Krishna et al, 2021). A shopping trip budget determines a consumer's buying power, and a larger budget can trigger positive emotions resulting in impulse buying (Badgaiyan & Verma, 2015; Chang et al, 2014).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Consumer-related factors Three consumer-related factors derived from impulse buying literature act as antecedents of impulse buying behaviour: consumer characteristics (Miao et al, 2019;Parsad et al, 2021), self-control (Nghia et al, 2021;Sun et al, 2021) and consumer resources (Atulkar & Kesari, 2018;Krishna et al, 2021). These variables are further explained below.…”
Section: Antecedents Of Impulse Buyingmentioning
confidence: 99%
“…Numerous studies have shown that individuals’ traits, tendencies, and styles can influence their psychological and behavioral performance, along with temporary priming manipulations, such as trait power and state power ( Schmidt-Barad and Uziel 2020 ), trait mindfulness and state mindfulness ( Egan et al 2018 ), trait attachment and attachment priming ( Cuyvers et al 2022 ), and chronic regulatory focus and situational regulatory focus, etc. ( Krishna et al 2021 ). Thinking styles reflect the relatively stable tendency of individuals to rely on the two processing modes, and they may interact with analytic processing priming.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individual regulatory focus affects consumer behaviors, such as advertising acceptance intention and impulsive consumption, in different ways (Gao et al , 2020; Krishna et al , 2021), and understanding user-centered factors can help explain their potential effects on individuals' participation in the VCC thinking process (Naletelich and Spears, 2020). Regulatory focus captures the final state of the goal pursuit process, in which the goal is to “approach gains and avoid nongains” or “approach nonlosses and avoid losses” (Pham et al , 2023).…”
Section: Literature Reviewmentioning
confidence: 99%